2021
DOI: 10.1029/2021ja029284
|View full text |Cite
|
Sign up to set email alerts
|

Van Allen Probes Observations of Multi‐MeV Electron Drift‐Periodic Flux Oscillations in Earth's Outer Radiation Belt During the March 2017 Event

Abstract: Radiation belt electrons undergo frequent acceleration, transport, and loss processes under various physical mechanisms. One of the most prevalent mechanisms is radial diffusion, caused by the resonant interactions between energetic electrons and ULF waves in the Pc4‐5 band. An indication of this resonant interaction is believed to be the appearance of periodic flux oscillations. In this study, we report long‐lasting, drift‐periodic flux oscillations of relativistic and ultrarelativistic electrons with energie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 86 publications
(137 reference statements)
0
15
0
Order By: Relevance
“…Future work using satellites with coverage of higher latitudes, such as Arase, will provide a better view of the distribution of drift-periodic flux oscillations at a broader range of latitudes and shed light on a deeper understanding of the latitudinal dependence of this phenomenon. Some recent event studies on flux oscillations suggested the potentially important role of local PSD radial gradient (e.g., Hartinger et al, 2020;Sarris et al, 2021;Zhao et al, 2021). Thus, we also explore the role of electron PSD radial gradient using the statistical approach.…”
Section: Statistical Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Future work using satellites with coverage of higher latitudes, such as Arase, will provide a better view of the distribution of drift-periodic flux oscillations at a broader range of latitudes and shed light on a deeper understanding of the latitudinal dependence of this phenomenon. Some recent event studies on flux oscillations suggested the potentially important role of local PSD radial gradient (e.g., Hartinger et al, 2020;Sarris et al, 2021;Zhao et al, 2021). Thus, we also explore the role of electron PSD radial gradient using the statistical approach.…”
Section: Statistical Resultsmentioning
confidence: 99%
“…Some recent event studies on flux oscillations suggested the potentially important role of local PSD radial gradient (e.g., Hartinger et al., 2020; Sarris et al., 2021; Zhao et al., 2021). Thus, we also explore the role of electron PSD radial gradient using the statistical approach.…”
Section: Statistical Resultsmentioning
confidence: 99%
See 3 more Smart Citations